Impact of Psychosocial Risk on the Work Environment, CaseHotels in the Municipality of Acapulco de Juárez, Guerrero - Yáñez Falcón de la Barrera, Ángel Alfredo; Cruz De los Ángeles, José Aurelio; Martínez Ángeles, Dulce María (HITOS DE CIENCIAS ECONÓMICO ADMINISTRATIVAS, 2024)
OBJETIVE: To identify whether psychosocial risks caused by hurricane Otis affect the staff working in SMEs in the hotel sector of the Municipality of Acapulco de Juárez, Guerrero. MATERIAL AND METHOD: A simple random probability sampling with a finite population was applied, using a confidence level of 90% (Z value=1.65) with a statistical error of 10%. Since the population size to be considered is known, the sample corresponding to 68 workers in the hotel sector was applied. RESULTS: 68% of respondents answered the following: psychosocial risks affected the work environment, 63% responded that the hurricane intensified these risks, 76% stated that psychosocial risks due to the hurricane continue to affect the work environment, and 66% experienced severe traumatic events. CONCLUSIONS: The items most closely related to psychosocial risks were: feelings and mutual trust; the greater the feeling generated in the work activity, the work environment worsens; the greater the mutual trust, the work environment gets worse.